Relationship between muscle volume and muscle torque of the hamstrings after anterior cruciate ligament reconstruction - Konishi, Y.; Fukubayashi, T. (Journal of Science and Medicine in Sport, 2010)
The muscle torque per unit volume of the hamstrings on the injured and uninjured sides in patients with ACL reconstruction were compared with participants with no history of knee injury to examine whether a similar mechanism leading to quadriceps weakness exists in the hamstrings of these patients. The study population consisted of 18 and 52 patients at <=6 and 12 months after ACL reconstruction, respectively, and 35 healthy controls. The hamstring volume was measured on MRI. To identify the muscle torque per unit volume, the peak torque of knee flexion was divided by the hamstring volume. Most muscle torque per unit volume indexes were not significantly different between the patients at <=6 months (injured side: 0.133 ± 0.03 N m/cm3, 60°/s; 0.107 ± 0.03 N m/cm3, 180°/s; uninjured side: 0.139 ± 0.02 N m/cm3, 60°/s; 0.107 ± 0.02 N m/cm3, 180°/s) and controls (0.170 ± 0.05 N m/cm3, 60°/s; 0.121 ± 0.05 N m/cm3, 180°/s). However, the muscle torque per unit volume of patients at 12 months in both injured (0.118 ± 0.03 N m/cm3, 60°/s; 0.092 ± 0.02 N m/cm3, 180°/s) and uninjured sides (0.120 ± 0.03 N m/cm3 at 60°/s; 0.094 ± 0.02 N m/cm3, 180°/s) were significantly lower than those of controls (P < 0.01). We found no evidence of recruitment disorder in the hamstrings of the patients. The results of this study indicated that the mechanism of muscle weakness of the hamstrings after reconstruction was different from that of the quadriceps, although the precise mechanism remains to be determined.